Gaze strategies in skateboard trick jumps: Spatiotemporal constraints in complex locomotion - Klostermann, A.; Küng, P. (Research Quarterly for Exercise and Sport, 2017)
Purpose: This study aimed to further the knowledge on gaze behavior in locomotion by studying gaze strategies in skateboard jumps of different difficulty that had to be performed either with or without an obstacle. Method: Nine experienced skateboarders performed "Ollie" and "Kickflip" jumps either over an obstacle or over a plane surface. The stable gaze at 5 different areas of interest was calculated regarding its relative duration as well as its temporal order. Results: During the approach phase, an interaction between area of interest and obstacle condition, F(3, 24) = 12.91, p < .05, np2 = .62, was found with longer stable-gaze locations at the takeoff area in attempts with an obstacle (p < .05, np2 = .47). In contrast, in attempts over a plane surface, longer stable-gaze locations at the skateboard were revealed (p < .05, np2 = .73). Regarding the trick difficulty factor, the skateboarders descriptively showed longer stable-gaze locations at the skateboard for the "Kickflip" than for the "Ollie" in the no-obstacle condition only (p>.05, d = 0.74). Finally, during the jump phase, neither obstacle condition nor trick difficulty affected gaze behavior differentially. Conclusions: This study underlines the functional adaptability of the visuomotor system to changing demands in highly dynamic situations. As a function of certain constraints, different gaze strategies were observed that can be considered as highly relevant for successfully performing skateboard jumps.